Hyperrreality in Avatar Film as a Form of Hegemony, Domination, and Capi-talist Ideology in Facing Society 5.0 - Hayati, Kinanti Resmi; Afdholy, Nadia; Nashahta, Terra Bellatrix Aden (Future Science)
Indonesia is a country with third world values, which in the context of international structure is called periphery. The flow of information from the central countries (especially America) has been moving rapidly to Indonesia, not only in the form of economic activities but also in culture. The spread of culture is felt especially with films and television media. Today's globalization enables the mass media industry to create a mass culture and deliver messages to the masses. Capitalist ideology perpetuates the power of the masses by uniforming and homogeneity of events (identical). The film presents a variety of images that provide a stronger illusion related to understanding reality. Generally, film and society are understood as something linear, in the sense that film always influences society based on the content of its mandate without ever having the opposite. Avatar is a fictional film that takes us on a vacation to a planet that seems so real, where natural resources have been overused for decades. Through the film Avatar, the occurrence of hegemony, domination, and capitalist ideology can be seen from the image deliberately done by producers to accompany the masses on a mass culture product. The contents of the media present simulacra, pseudo needs, and create a pseudo world (hyperreality).